2021
DOI: 10.1590/1413-785220212904241563
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Injuries Occurred During Brazilian Football Championship in 2019

Abstract: Objective: To determine the incidence and risk factors for injuries that occurred during the matches of the Brazilian Football Championship. Methods: A prospective study was carried out with the collection of data referring to injuries that occurred during the 2019 Brazilian Football Championship. The injuries were recorded by the responsible physician of each team, through an online injury mapping system. Results: Among the 645 athletes who were included in the study, 214 (33.2%) of the players had at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
3
0
3
Order By: Relevance
“…Our study identified a FIFA index of 2.00 for ankle sprains, a value higher than upper limb injuries (FIFA index ¼ 1.34) 5 and ruptures of the anterior cruciate ligament (FIFA index ¼ 0.41), 6 but lower than muscle injuries (FIFA index ¼ 7.66). 7 A German study with Bundesliga (the German professional football league) athletes observed 280 episodes of ankle sprains (5.17% of total injuries) from the 2008 to 2014 seasons. This study reported a rate of 46.66 injuries per year, which represents a difference of 35.55% concerning our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study identified a FIFA index of 2.00 for ankle sprains, a value higher than upper limb injuries (FIFA index ¼ 1.34) 5 and ruptures of the anterior cruciate ligament (FIFA index ¼ 0.41), 6 but lower than muscle injuries (FIFA index ¼ 7.66). 7 A German study with Bundesliga (the German professional football league) athletes observed 280 episodes of ankle sprains (5.17% of total injuries) from the 2008 to 2014 seasons. This study reported a rate of 46.66 injuries per year, which represents a difference of 35.55% concerning our study.…”
Section: Discussionmentioning
confidence: 99%
“…Em nosso estudo identificamos um índice FIFA de 2,00 para as entorses de tornozelo, um valor superior às lesões do membro superior (índice FIFA ¼ 1,34) 5 e rupturas do ligamento cruzado anterior (índice FIFA ¼ 0,41), 6 porém inferior às lesões musculares (índice FIFA ¼ 7,66). 7 Em um estudo alemão que avaliou atletas da Bundesliga (liga alemã de futebol profissional) nas temporadas de 2008 a 2014, foram observados 280 episódios de entorses do tornozelo (5,17% do total de lesões) com uma taxa de 46,66 lesões por ano, o que representa uma diferença de 35,55% em relação ao nosso estudo. 3 Árnason et al 8 avaliaram 10 clubes da elite do futebol islandês, e do total de lesões encontradas, 82% localizavam-se nos membros inferiores.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Outra possibilidade que pode explicar essa prevalência é o fato dos esportes mais praticados no Brasil serem o futebol e o vôlei, os quais apresentam maior incidência de lesões em membros inferiores. 24,25 Outro importante ponto analisado pelo presente estudo foi a fonte de busca sobre estes instrumentos de avaliação. A maior parte das escalas funcionais utilizadas nas áreas ortopédica e esportiva são de origem estrangeira e precisam passar pelo processo de tradução e validação para população brasileira para que sejam utilizadas.…”
Section: Discussionunclassified